2015
DOI: 10.3402/meo.v20.29221
|View full text |Cite
|
Sign up to set email alerts
|

A time-efficient web-based teaching tool to improve medical knowledge and decrease ABIM failure rate in select residents

Abstract: AimThe American Board of Internal Medicine (ABIM) exam's pass rate is considered a quality measure of a residency program, yet few interventions have shown benefit in reducing the failure rate. We developed a web-based Directed Reading (DR) program with an aim to increase medical knowledge and reduce ABIM exam failure rate.MethodsInternal medicine residents at our academic medical center with In-Training Examination (ITE) scores ≤35th percentile from 2007 to 2013 were enrolled in DR. The program matches reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Some of the remediation plans include enrolling in board review courses, attending conferences, or self-study courses, however, their efficacy in helping residents pass the ABIM-CE is unclear [29]. Although there are reports of improved ABIM-CE results with a directed reading program and individual education plan, although literature regarding the efficacy of these strategies is limited [30,31]. At our program, we identified residents with scores < 35 percentile in the PGY3 ITE exam, and encouraged them to enroll in board review courses or use one of the available Question bank's which yielded a 100% ABIM-CE pass rate over the past few couple of years.…”
Section: Usmle Scores (Mean (Sd))mentioning
confidence: 99%
“…Some of the remediation plans include enrolling in board review courses, attending conferences, or self-study courses, however, their efficacy in helping residents pass the ABIM-CE is unclear [29]. Although there are reports of improved ABIM-CE results with a directed reading program and individual education plan, although literature regarding the efficacy of these strategies is limited [30,31]. At our program, we identified residents with scores < 35 percentile in the PGY3 ITE exam, and encouraged them to enroll in board review courses or use one of the available Question bank's which yielded a 100% ABIM-CE pass rate over the past few couple of years.…”
Section: Usmle Scores (Mean (Sd))mentioning
confidence: 99%
“…As previously mentioned, residency programs in various specialties have developed a range of curricular interventions to improve the ITE scores as means of achieving a higher first-time board examination pass rate [ web-based directed reading program with an aim to increase medical knowledge and reduce ABIM exam failure rate [23]. Their strategy involved identifying incorrectly answered ITE educational objectives and encouraging residents to type a 'reflection' representing their understanding of the educational objective.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified specific cutoffs for ITE percentile ranking as predictors of successful first-time ABIM certification exam pass [8][9][10][11]. Accordingly, residency programs in various specialties have developed a range of curricular interventions, including frequent faculty meetings, instilling educational conferences, developing individualized study plans, and providing online cases, practice questions, group learning scenarios, and customized web-based teaching tools, to improve the ITE scores as means of achieving a higher first-time board examination pass rate [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The exact nature and efficacy of remediation plans, including board review courses, conferences or self-study courses, in helping the resident pass the ABIM-CE are unclear [30]. Although there have been reports of improved ABIM-CE results with a directed reading program and individual education plan for residents, literature regarding the efficacy of these strategies is limited [31,32]. Furthermore, there are many other unexplained factors determining whether a resident passes an ABIM-CE.…”
Section: Discussionmentioning
confidence: 99%